Ecological effects of Irgarol 1051 and Diuron on a coastal meiobenthic community: A laboratory microcosm experiment - Gallucci, Fabiane; De Castro, Italo Braga; Perina, Fernando Cesar [UNESP]; De Souza Abessa, Denis Modelo [UNESP]; De Paula Teixeira, Amanda (Elsevier, 2015)
After the Tributyltin world ban, Irgarol 1051 and Diuron have been the most commonly used biocides in antifouling paints. When adsorbed to suspended particulate matter or introduced as paint particles, these compounds accumulate in marine sediments and potentially cause ecological damage to benthic organisms. Therefore, a microcosm experiment was designed to evaluate the effects of Irgarol 1051 and Diuron, individually, on a meiofaunal community with emphasis on the dominant nematode assemblages. The experiment tested two factors: Treatment (two types of controls and three environmentally relevant concentrations of each contaminant) and Exposure time (5, 15 and 30 days). Significant declines in meiofauna density, nematode species richness and diversity, and changes in multivariate community structure were observed for both biocides at all exposure levels when compared to controls. Decreases occurred early on, within five days of exposure, which suggests that mortality, and not sub-lethal effects, has befallen upon the organisms. Sediment chlorophyll a and pheopigment concentrations, and redox potential were monitored to verify any indirect effects to the fauna through changes in the environment and results gave no indications of such mediated effects pointing to a direct toxic effect of both Irgarol and Diuron on the meiofauna. Although contaminated treatments showed a significant decline in the relative abundances of a particular functional group represented by the larger, longer-lived species, we did not observe the typical expected switch to smaller, more opportunistic taxa. Indeed, differences between controls and contaminated treatments were mainly due to an overall reduction in densities of the most abundant species in contaminated treatments. The high mortality (ca. 50% decline in total abundances), changes in community structure and species loss observed at biocide levels frequently encountered in the field suggest Irgarol and Diuron as a threat to benthic communities. Such severe effects contrast to other studies that have detected lower impacts, suggesting the free-living nematodes as potential indicators of marine pollution and the microcosm approach using natural communities as an impending tool for ecotoxicological studies.
Keywords: Antifouling paints; Booster biocides; Ecotoxicology; Meiofauna; Microcosm; Nematode